ANALISIS KESADARAN HUKUM MASYARAKAT TERHADAP BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DIHUBUNGKAN DENGAN PERNIKAHAN DAN PERCERAIAN DI WILAYAH KABUPATEN BOGOR - endeh suhartini (Universitas Djuanda Bogor, 2011)
tying soul and physic of a man and a woman as a couple of wife and husband with a target to happy and everlasting family forming according to Belief in the one and only God Society sense of justice about applying Marriage Act had not been matching with expected. Social sense of justice concerning science aspect, appreciation and compliance of the parties to finishing all the dispute according to the law. Hence from that, the government must be giving some facilities to increase the society sense of justice about applying marriage act through research, dissemination or devotion to knowing the Society sense of justice about applying act in Indonesia. Target of this research is to know the efforts of Regency Bogor Government about applying marriage act, and also to know the causing of divorce factors attributed to society sense of justice about applying marriage act of Bogor Regency by taking information and data from some countryside in three sub district as an input and information research According to fact finding result in the field research that society sense of justice at some region do not full of awareness own of applying marriage act especially in cloistered which is far from Governance Center. This Matter is caused of less science understanding, transportation difficulty band, communication and of economic condition. But there is also more region which respecting of moslem scholar / moslem leader according to Islamic Law to execute the Marriage without applying Marriage Act and the divorce in cloistered region is do not through Islamic Religion Justice caused of the marriage is not noted in KUA and have not own the marry book so that certainty law guarantee for the marriage is executed un expectation.